Legal Protection Of The Injured Parties Due To The Cancellation Of The Deed Of Sale - Savira Damayanti; Agung Iriantoro; Endah Triwulandari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
AJB is an authentic document whose validity is highly dependent on the manufacturing process that must meet legal provisions, one of which is the presence of the parties and PPAT when making and signing the Acte. The presence of PPAT is absolute because it acts as a state official who guarantees the formal and material truth of the contents of the Acte and explains the legal consequences of the transaction to the parties. This type of research is normative law research, with a study of legal materials containing normative legal rules. This research relates to legal norms that exist in society and in legislation and court decisions. In Indonesia Civil Code Clause 1338 Verse 3, good faith is only mentioned in relation to the making of treatys, but is not regulated further. Therefore, in SEMA Number 4 of 2016, buyers who have good faith are given a guarantee in the form of legal protection. Good faith itself consists of two types, namely subjective, which is interpreted as honesty, and objective, which is interpreted as a form of politeness and manners, whereby a person must also comply with social norms. A buyer acting in good faith is a buyer who carefully examines the physical condition and legal data of a transfer of land rights being purchased, both before and at the time of transfer. However, if the buyer is aware of a defect in the transfer of rights process, the buyer's good faith is considered lost. Legal protection for buyers is only for buyers acting in good faith. In the cancellation of an AJB, protection for buyers is in the form of a civil lawsuit against the deed and compensation. Under certain conditions, an agreement may be cancelled, either by the parties or by court order. As a form of binding agreement, a land sale and purchase agreement contains the rights and obligations of the parties who made it, so that if the terms agreed upon in the sale and purchase agreement are violated or not fulfilled by the parties who made it, then it can be said that there has been a breach of contract. Before a sale and purchase can be carried out before an authorised official, namely the Land Deed Official (PPAT), the parties who will sell and purchase land rights must meet all the requirements stipulated for the sale and purchase of land. Requirements regarding the object of sale and purchase, for example, the land rights to be sold and purchased are legally owned by the seller, as evidenced by a land certificate or other valid proof of such rights, and the land being sold and purchased is not in dispute with other parties, and so on